2005
DOI: 10.1348/000712605x47422
|View full text |Cite
|
Sign up to set email alerts
|

Face processing and familiarity: Evidence from eye‐movement data

Abstract: How is information extracted from familiar and unfamiliar faces? Three experiments, in which eye-movement measures were used, examined whether there was differential sampling of the internal face region according to familiarity. Experiment 1 used a face familiarity task and found that whilst the majority of fixations fell within the internal region, there were no differences in the sampling of this region according to familiarity. Experiment 2 replicated these findings, using a standard recognition memory para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 22 publications
10
56
1
Order By: Relevance
“…We would thus suggest that the nose was fixated in the study of Hsiao and Cottrell (2009), not the center of the face. Our findings reinforce the hypothesis that observers rely on information from internal features in various face recognition tasks, as has been shown to be the case in identification and familiarity rating (Stacey, Walker, & Underwood, 2005). Thus, if a ''center of information'' as proposed by Hsiao and colleagues exists, this center is clearly different from the geometrical center of a face.…”
Section: Features Always Mattersupporting
confidence: 84%
“…We would thus suggest that the nose was fixated in the study of Hsiao and Cottrell (2009), not the center of the face. Our findings reinforce the hypothesis that observers rely on information from internal features in various face recognition tasks, as has been shown to be the case in identification and familiarity rating (Stacey, Walker, & Underwood, 2005). Thus, if a ''center of information'' as proposed by Hsiao and colleagues exists, this center is clearly different from the geometrical center of a face.…”
Section: Features Always Mattersupporting
confidence: 84%
“…Since the seminal work by Yarbus (1967) on eye movements to faces in the 1960s, studies have reported a consistent pattern of results whereby fixations are predominantly directed to the eyes, followed by the nose, and mouth (e.g., Althoff & Cohen, 1999;Luria & Strauss, 1978;Mertens, Siegmund, & Grüsser, 1993;Stacey, Walker, & Underwood, 2005). This viewing pattern might reflect an automatic preference for the eye region because it conveys information diagnostic for identifying individual faces (e.g., Barton et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…In recent years, several studies have explored the relationship between recognition of faces and gaze fixations (e.g., Althoff & Cohen, 1999;Hannula et al, 2010;Ryan, Hannula, & Cohen, 2007;Stacey, Walker, & Underwood, 2005). The leading question has been whether prior experience with a face determines subsequent eye movement behavior.…”
Section: Abstract Eye Movements Concealed Information Test Guiltymentioning
confidence: 99%